'The bell was tolling': the framing of religious freedom in The Australian editorials 2015-2019. Issue 3 (1st September 2020) - Poulos, Elenie
ABSTRACT: The Australian is one of the country's most politically influential newspapers. Between 2015 and 2019 it ran a campaign, supported by an unusually large number of editorials, which raised the profile of the issue of religious freedom in public debate. This article uses media framing analysis to examine the 40 editorials that addressed religious freedom published during this period. Religious freedom was framed by The Australian as a right under profound threat which could have significant consequences for Australian society. The analysis also shows, however, that the framing of religious freedom—and the intertwined freedoms of speech and conscience—was deliberately constructed in order not to protect and promote these rights, but to undermine the progress of LGBTIQ rights, and marriage equality in particular. In the clash between The Australian's avowed libertarian principles and its politically conservative policy agenda, the newspaper used its framing of religious freedom to continue its longstanding campaign against the progressive left.